Depleting Ly6G Positive Myeloid Cells Reduces Pancreatic Cancer-Induced Skeletal Muscle Atrophy - Michael R. Deyhle; Chandler S. Callaway; Daria Neyroud; Andrew C. D’Lugos; Sarah M. Judge; Andrew R. Judge (Cells, 2022)
Immune cells can mount desirable anti-cancer immunity. However, some immune cells can support cancer disease progression. The presence of cancer can lead to production of immature myeloid cells from the bone marrow known as myeloid-derived suppressor cells (MDSCs). The immunosuppressive and pro-tumorigenic effects of MDSCs are well understood. Whether MDSCs are involved in promoting cancer cachexia is not well understood. We orthotopically injected the pancreas of mice with KPC cells or PBS. One group of tumor-bearing mice was treated with an anti-Ly6G antibody that depletes granulocytic MDSCs and neutrophils; the other received a control antibody. Anti-Ly6G treatment delayed body mass loss, reduced tibialis anterior (TA) muscle wasting, abolished TA muscle fiber atrophy, reduced diaphragm muscle fiber atrophy of type IIb and IIx fibers, and reduced atrophic gene expression in the TA muscles. Anti-ly6G treatment resulted in greater than 50% Ly6G+ cell depletion efficiency in the tumors and TA muscles. These data show that, in the orthotopic KPC model, anti-Ly6G treatment reduces the number of Ly6G+ cells in the tumor and skeletal muscle and reduces skeletal muscle atrophy. These data implicate Ly6G+ cells, including granulocytic MDSCs and neutrophils, as possible contributors to the development of pancreatic cancer-induced skeletal muscle wasting.